Estado nutricional e ingesta de sodio en la dieta de adultos con y sin hipertensión arterial, Ibarra 2022: Nutritional status and dietary sodium intake in adults with and without arterial hypertension, Ibarra 2022 (La U Investiga, 2024)
The prevalence of arterial hypertension (HTN) has increased globally. Environmental factors such as diet have a great influence on this pathology, particularly high sodium (Na) intake is considered an important factor. This study aimed to determine the nutritional status and dietary sodium intake in adults with and without arterial hypertension in the city of Ibarra 2022. A cross-sectional quantitative descriptive study was carried out in 40 adults, 20 hypertensive and 20 non-hypertensives. Nutritional status was assessed through body mass index and weekly sodium intake through a semi-quantitative food frequency questionnaire (CFCA). 65.00% were women, the age was 43.20±12.10 years, 72.50% were mestizos and more than half had higher education (62.50%). A BMI of 24.45±3.31 kg/m2 was found, a weekly Na consumption of 14.34±6.45 g and 60% had a normal nutritional status. The weekly g of Na consumed were not different between people with and without hypertension (9.80±9.76 vs 10.18±7.38 g; p=0.904), however, the BMI was significantly different between these groups (26.49 ± 3.07 vs 23.40 ± 3.29 g, p=0.048). Additionally, 60% of those studied perceived to have a low consumption of Na. In conclusion, it would be said that less than half of those studied were overweight or obese, however, the BMI is significantly higher in hypertensive patients and sodium consumption is not different in adults with and without hypertension.
Keywords: nutritional status, sodium, arterial hypertension, dietary intake